The Influence of Quality of Service and Customer Satisfaction With Customer Loyalty at PT. Bank Shinhan Indonesia Bandung Cihampelas Branch - Erpurini, Wala (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2021)
This research was conducted at PT. Bank Shinhan Indonesia Bandung Branch Cihampelas a company engaged in the services of the Bank. The purpose of this research is to see the influence of quality of service and customer satisfaction on customer loyalty in PT. Bank Shinhan Indonesia Bandung Branch Cihampelas. Researchers used purposive sampling techniques and used questionnaires as data retrieval methods. For associative analysis using, path analysis, and coefficient of determination analysis. In addition, validity tests and reliability tests are carried out to determine accuracy in data measurement. Based on the results of the study showed the average score of service quality variables is 310.1 categorized as